Systemic Impact of Subgingival Infection Control in Periodontitis Patients with Cardiovascular Disease: A Narrative Review - Carmen Silvia Caloian; Andreea Ciurea; Marius Negucioiu; Alexandra Roman; Iulia Cristina Micu; Andrei Picoș; Andrada Soancă (MDPI AG, 2024)
Introduction: Periodontitis, an infectious inflammatory condition, is a key contributor to sustained systemic inflammation, intricately linked to atherosclerotic cardiovascular disease (CVD), the leading cause of death in developed nations. Treating periodontitis with subgingival mechanical instrumentation with or without adjunctive antimicrobials reduces the microbial burden and local inflammation, while also potentially bringing systemic benefits for patients with both periodontitis and CVD. This review examines systemic effects of subgingival instrumentation with or without antimicrobial products in individuals with periodontitis and CVD, and explores intricate pathogenetic interactions between periodontitis and CVD. Material and Methods: English-language databases (PubMed MEDLINE and Cochrane Library) were searched for studies assessing the effects of nonsurgical periodontal therapies in periodontitis patients with or without CVD. Results: While the ability of periodontal therapy to reduce mortality- and morbidity-related outcomes in CVD patients with periodontitis remains uncertain, some studies indicate a decrease in inflammatory markers and blood cell counts. Subgingival mechanical instrumentation delivered over multiple short sessions carries lower risks of adverse effects, particularly systemic inflammation, compared to the full-mouth delivery, making it a preferable option for CVD patients. Conclusions: Subgingival mechanical instrumentation, ideally conducted in a quadrant-based therapeutic approach, to decontaminate periodontal pockets has the potential to reduce both local and systemic inflammation with minimal adverse effects in patients suffering from periodontitis and concurrent CVD.